Risks of Iodine Excess - Sohn, Seo Young; Inoue, Kosuke; Rhee, Connie M; Leung, Angela M (Endocrine reviews, 2024)
Abstract Iodine is a micronutrient that is required for thyroid hormone synthesis. The iodide cycle in thyroid hormone synthesis consists of a series of transport, oxidation, organification, and binding/coupling steps in thyroid follicular cells. Common sources of iodine include the consumption of an iodine-rich diet or iodine-fortified foods, the administration of amiodarone, iodine-containing supplements, or iodinated contrast media, and other miscellaneous sources. Methods to assess population iodine status include the measurement of urinary iodine concentrations, blood thyroglobulin levels, prevalence of elevated neonatal thyrotropin levels, and thyroid volume. Although excessive iodine intake or exposure is generally well tolerated, an acute iodine load may result in thyroid dysfunction (hypothyroidism or hyperthyroidism) in certain susceptible individuals due to the failure to escape from the Wolff–Chaikoff effect and to the Jod–Basedow phenomenon, respectively. In this review, we discuss the associations between excessive iodine intake or exposure, with particular focus on iodinated contrast media as a common source of excess iodine in health care settings, and risks of incident thyroid dysfunction. We also summarize the risks of iodine excess in vulnerable populations and review current guidelines regarding the screening and monitoring of iodinated contrast–induced thyroid dysfunction. Finally, we discuss the long-term potential nonthyroidal health risks associated with iodine excess and suggest the need for more data to define safe upper limits for iodine intake, particularly in high-risk populations. Graphical Abstract Graphical Abstract